2012
DOI: 10.1308/003588412x13171221590971
|View full text |Cite
|
Sign up to set email alerts
|

Safety trial of Floseal® haemostatic agent in head and neck surgery

Abstract: INTRODUCTIONFloseal® (Baxter, Hayward, CA, US) can be of value in reducing blood loss and haematoma rates. The manufacturer’s warnings include allergic reaction, poor wound healing and intravascular thrombosis. We aimed to determine whether Floseal® is safe to use in various head and neck surgery (HNS) procedures.METHODSA prospective trial was conducted using Floseal® in 42 various consecutive head and neck surgery procedures. Adverse incidents were used as the main outcome measure, including allergic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…More recently FloSeal has been described for other purposes such as providing hemostasis after tonsillectomy with cold steel dissection . Ujam et al studied the incidence of adverse effects when utilizing FloSeal in 42 consecutive head and neck procedures, and found it to be a safe and effective hemostatic agent …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently FloSeal has been described for other purposes such as providing hemostasis after tonsillectomy with cold steel dissection . Ujam et al studied the incidence of adverse effects when utilizing FloSeal in 42 consecutive head and neck procedures, and found it to be a safe and effective hemostatic agent …”
Section: Discussionmentioning
confidence: 99%
“…9 Ujam et al studied the incidence of adverse effects when utilizing FloSeal in 42 consecutive head and neck procedures, and found it to be a safe and effective hemostatic agent. 10 Furthermore, FloSeal has been studied in epistaxis with great success when compared to nasal packing. Mathiasen and Cruz compared FloSeal to nasal packing in a prospective, randomized, controlled trial of 70 consecutive patients presenting with acute anterior epistaxis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Floseal is a combination gelatin-thrombin tissue sealant composed of human thrombin and bovine-derived gelatin, mixed in saline. 25 Floseal requires reconstitution in calcium chloride before use, 6 which requires 60 seconds of preparation time. It is then extruded like a paste from a syringe to provide more precise application.…”
Section: Normal Hemostasis Includes a Vascular Component A Platelet mentioning
confidence: 99%
“…[19][20][21] For neurosurgical procedures, only studies that evaluate their efficacy during both brain and spine surgery have been published. 2,5,[22][23][24][25][26][27][28][29][30][31] To date, only one study focused exclusively on the use of a thrombin gelatin hemostatic matrix in spinal surgery (Surgiflo), 32 but there are no comparative studies between the two products in spinal surgery. One study reported on a rat model of laminectomy.…”
Section: Introductionmentioning
confidence: 99%